Socio- Economic Variables and its Impact on Agricultural Development among Tribal Farming Community in North-East Hill Region - Bihari, Bankey; Singh, Ummed (Indian Journal of Hill Farming, 2017)
India as a country may be self-sufficient in food grain production but most of the states are still starving and are unable to produce sufficient foodgrain to meet out their requirements. Almost all the N.E. States are also in the same category where maximum population is of tribals who still live in primitive conditions without basic amenities. In India about 461 tribes are there with the total population of about 677 lakhs who mostly live in hilly and remote areas. Out of that about 147 tribes are there in north east with the total population of about 81 lakhs. Alone in Meghalaya total 13 tribes are there & their population is about 15 lakhs. Major are Khasi, Garo and Jaintia with about 80.33% of the State’s total population. A study was conducted in the state of Meghalaya to explain the socio-economic scenario of the tribal farmers and its impact on overall agricultural development. To measure the socioeconomics of the tribal farmers 100 point socio-economic status Index (SESI) was developed with three major components viz. Personal factors, social factors and economic factors with weighted value of 31,16 & 53 respectively. It is evident from the weighted value that economic factors constribute much more to the overall socio-economic status. For data collection one district from each of three major tribes viz. Khasi, Garo and Jaintia was selected and from these three districts three blocks, from each block two villages (one progressive & one non-progressive) and from each village 30 respondents (Total-180, 90 from progressive and 90 from non-progressive villages) were taken for the study. Results revealed that irrespective of Khasi, Garo or Jaintia, progressive villages had high (62.73, 61.50 & 59.93 respectively) SESI value in comparison to non-progressive villages (54.86, 55.0 & 53.13 respectively), all significant at 1% level. But adoption of improved technologies was found to be very low among 73.3% of total respondents followed by medium among 20.5% and high among 6.1%. Though difference between adoption level of progressive & non-progressive farmers was observed but it was non-significant. Reasons for low adoption level among all the categories might be attributed to the complex social system, land tenure system and the remoteness of the area in terms of basic infrastructure and communication facilities where about 27.0% farmers are still practising shifting cultivation. For such a situation promotion of other enterprises viz. Piggery, Poultry, Beekeeping, Goat rearing etc. may be suggested as a short term measures where so far neglected areas and downtrodden should be the target. In long run, for improvement in the overall situation land reforms along with intensive educational and capacity building programmes may provide the real base for desired agricultural development in the state of Meghalaya as well as in whole north-east India.